Pengaruh Design Produk dan Digital Marketing terhadap Minat Beli Album Fisik Musik K-Pop di Indonesia - Febrianti; Ajat Sudrajat (Faculty of Economics and Business, University of Pancasakti Tegal, 2021)
Design product consists of color, shape, apperance and function that could be seen and felt by consumers. Digital marketing is one of the marketing methods used by companies to promote its products. This study aims to determine the effect of Design product and Digital marketing on the Interest in buying a physical album of K-Pop music in Indonesia. This type of research is quantitative research. The population is fans of K-Pop music in Indonesia. The number of samples is 100 respondents. The sampling technique used was purposive sampling. Test instruments using validity and reliability tests. The analysis technique used is multiple linear regression. The results of this study indicate that Design product and Digital marketing have a significant effect on the interest in buying physical albums of K-Pop music in Indonesia.